Tam$1 (Bs slipper :s a story from Vietnam - Palazzo-Craig, Janet; Nagano, Makiko ([Mahwah, N.J.] : Troll, 1996)
In this Vietnamese version of the Cinderella story, a mysterious woman dressed in the royal colors of orange and yellow provides Tam with beautiful clothes, slippers, and a horse to go to the harvest festival.
Keywords: Folklore -- Vietnam